A Study on Consumer Trust, Value and Loyalty in Relational Exchanges - Balasubramanian, N.; Sathyanarayan, K. (Indian Journal of Marketing, 2008)
The Success of any business lies in maintaining a strong base of loyal customers. The organization exists for the customers and the customers are the deciding forces behind success or failure of a business organization. Keeping the customers and ensuring customer satisfaction is thus very crucial for the success and growth of all service firms, no matter what is the size or nature of the business. The growing importance of relationship marketing has heightened interest in the role of trust in fastening strong relationships.